Deformation Rules for Surrounding Rock in Directional Weakening of End Roofs of Thin Bedrocks and Ultrathick Seams - Fei Liu; Zhanguo Ma; Yongsheng Han; Zhimin Huang (Advances in Civil Engineering)
With the deployment of China’s energy strategy in the western regions, complex geological mining conditions such as thin bedrock and ultrathick seams in western China have caused a series of problems such as serious deformation of the surrounding rock at the ends of the working face and the increase in the lead abutment pressure of the roadways; the research on end roof deformation in the resource exploitation in western China has become one of the great demands of the industry. Based on the failure characteristics of rock mass, relying on the actual mining geological conditions of a coal mine in Inner Mongolia, the failure characteristics of the overlying rock strata under the influence of mining were simulated and analyzed using similar material simulation experiment, which intuitively reproduced the failure and deformation processes of the immediate roof, main roof, and key strata and revealed the mechanical mechanism of the directional weakening of the end roof. It is of great significance for the stability control of the surrounding rock at the end of the fully mechanized caving face in the thin bedrocks and ultrathick seams, reducing the abutment pressure of gate roadway and controlling the spontaneous combustion of residual coal in the goaf.